Phase demodulation of hybrid 3×3 coupler and Sagnac interferometer for φ-OTDR - Yang, Binyuan; Wang, Tingyu; Zhang, Jianzhong; Ma, Zhe; He, Xiang; Liu, Lipu; Wang, Yixuan; Zhang, Mingjiang (Frontiers in Physics, 2025)
A hybrid phase demodulation structure combining a 3 × 3 coupler and Sagnac interferometer is proposed to improve the spatial resolution and phase demodulation performance of the phase-sensitive optical time-domain reflectometer (φ-OTDR). Through: (1) identical optical path lengths in forward/reverse Sagnac paths resolving spatial resolution degradation caused by optical path differences in conventional schemes (e.g., 3 × 3 demodulation with unbalanced Michelson or Mach-Zehnder interferometers), and (2) SOA integration dynamically adjusting phase difference between paths to enhance signal-to-noise ratio (SNR) of three output signals, this design achieves high phase demodulation quality. Through theoretical analysis and numerical simulation, the performance enhancement effect of this structure has been verified. The results indicate that the SOA modulates the phase offset of the three output signals, significantly improving the phase demodulation quality and extending the amplitude and frequency response range of the system. Compared with the positioning results achieved by the unbalanced Michelson scheme, this method offers higher spatial resolution. Fundamentally, the structure eliminates path-imbalance limitations via Sagnac symmetry while SOA-driven SNR enhancement ensures robust performance.